Analisis Determinan Volume Ekspor Kopi Indonesia dari Sisi Permintaan - Fadhillah, Haris; Anward, Ryan Juminta (PPJP ULM, 2023)
Indonesia is the fifth largest coffee exporter in the world. However, the improvement of Indonesias coffee export volume experiences fluctuation every year and even tends to decrease. This occurs due to some factors that affect it. The objective of this study is to analyze what factors affect the coffee export volume from the demand side and the most dominant factor which affects the export volume of Indonesias coffee from the demand side. This study uses a linear regression data panel method with five destination countries. The data which are used are secondary data between 2003-2019. This study shows domestic coffee consumption and gross domestic product per capita affect positively and significantly. At the same time, the real exchange rate affects negatively and is significant to Indonesias coffee volume export. The variable of gross domestic product per capita is the most dominant factor of Indonesias coffee export volume.